Worlding of Space - James Cook's Travel Writing - Klepač, Tihana (2007)
Richard White discussed national identity as “ an invention, ” an “ intellectual construct” , each written text thus contributing to its formulation, and hence Cook's journals as well. North America and Australia were brought into script and thus consequently into existence in his writings (worlding, Spivak). However, mapping and describing the colony meant knowing it, and knowing it meant controlling it, and the “ debasement whereby the hill tribes are described … in terms of ‘ depravity’ , ‘ treachery’ , ‘ brutality’ and ‘ perfidy’ ", made the "surrender of their land an ‘ obligation’ " (Ashcroft 1999).